Generation of Immigration and Body Mass Index in Canadian Youth - Quon, Elizabeth C. (J Pediatr Psychol, 2012)
OBJECTIVE: To investigate the role of acculturation, as measured by generational status, on body mass index (BMI) in a sample of Canadian youth. METHODS: Population-based data from the National Longitudinal Survey of Children and Youth were used. Participants were divided into 2 age ranges: children aged 6–11 years (n = 14,287) and adolescents aged 12–17 years (n = 12,155). Youth were classified into one of five generations of immigration: first-generation, second-generation, mixed-generation, third-generation, and Aboriginal. Parent-and self-report height and weight were used to calculate BMI Z-scores. RESULTS: Generation of immigration was significantly related to BMI Z-score in both childhood and adolescence. First-generation immigrants had more weight gain compared to other groups during adolescence, but not during childhood. CONCLUSIONS: Acculturation, as measured by generation of immigration, is an important predictor of BMI in Canadian children and adolescents.